204 The role of immune checkpoint inhibitor as a single agent or combination therapy in advanced thyroid cancer. (10th December 2020) - Lee, Ju Young; Park, Inae; Nam, Myungwoo; Low, Christmann; Kim, Eugene; Choi, Hansol; Vagia, Elena; Jung, Chan Mi; Chae, Young Kwang
Abstract : Background: There is a high unmet need for effective systemic treatment for patients with metastatic radioactive iodine refractory (RAI-R) differentiated thyroid cancer (DTC) and anaplastic thyroid cancer (ATC). Immunotherapy may be used as an alternative option for those without targetable mutations or have become resistant to targeted therapy. Here we review the clinical trials and retrospective studies and discuss the potential role of immune checkpoint inhibitors (ICIs) in advanced thyroid cancer. Methods: The details of pertinent clinical trials were obtained from clinicaltrials.gov (NIH) using search terms including 'thyroid cancer' and 'immunologic.' The NCT numbers and search terms were used to search for published results on databases such as PubMed, American Association of Cancer Research, and American Society of Clinical Oncology. The efficacy outcome measures were determined using Response Evaluation Criteria in Solid Tumors (RECIST) v1.1. Results: In RAI-R DTC, responses to three different regimens have been reported: pembrolizumab, nivolumab plus ipilimumab, and pembrolizumab plus lenvatinib. No CR was reported, and the overall response rates (ORRs) varied from 9% (pembrolizumab monotherapy and nivolumab plus ipilimumab) to 64% (pembrolizumab plus lenvatinib) (figure 1 a). 1–4 In ATC, four studies have reported favorable outcomes in the context of dabrafenib and trametinib. 5 The efficacy of spartalizumab, a PD1-inhibitor, was evaluated in a phase I/II trial, rendering an ORR of 19%, with 3 CRs (7%) and 5 PRs (12%) [6]. The study of nivolumab plus ipilimumab reported an ORR of 30% in ATC, with a near CR and two without clear evidence of disease at 13 and 26 months. 2 A trial that tested the combination of atezolizumab, vemurafenib, and cobimetinib in BRAFV600E-mutated patients reported an ORR of 59%. 7 A retrospective study reported an ORR of 60% after adding pembrolizumab at the time of progression on lenvatinib 8 (figure 1 b). There are 25 ongoing trials evaluating the efficacy of ICIs in different types of thyroid cancer. Three trials are testing pembrolizumab as monotherapy, three trials are assessing ICI combination therapy, and six trials are testing the efficacy of various ICI and tyrosine kinase inhibitor (TKI) combinations (figure 2 ). Conclusions: The recent trials and a retrospective study have reported favorable outcomes in ATC, suggesting ICIs have a potential role in treating patients with ATC. In particular, dual ICIs or combination of TKI and ICI can be developed as treatment options for ATC. Further large scale randomized prospective studies are required to establish ICIs as standard of care. References: Mehnert JM, et al. Pembrolizumab for advanced papillary or follicular thyroid cancer: preliminary results from the phase 1b KEYNOTE-028 study. Journal of Clinical Oncology 2016; 34: 6091–6091. Lorch JH, et al. A phase II study of nivolumab (N) plus ipilimumab (I) in radioidine refractory differentiated thyroid cancer (RAIR DTC) with exploratory cohorts in anaplastic (ATC) and medullary thyroid cancer (MTC). Journal of Clinical Oncology 38, no. 15_suppl (May 20, 2020) 6513–6513. Haugen B, et al. Lenvatinib plus pembrolizumab combination therapy in patients with radioiodine-refractory (RAIR), progressive differentiated thyroid cancer (DTC): Results of a multicenter phase II international thyroid oncology group trial. Journal of Clinical Oncology 38, no. 15_suppl (May 20, 2020) 6512–6512. Schlumberger M, et al. Lenvatinib versus placebo in radioiodine-refractory thyroid cancer. N Engl J Med 2015; 372 :621–30. Subbiah V, et al. Dabrafenib and Trametinib Treatment in Patients With Locally Advanced or Metastatic BRAF V600-Mutant Anaplastic Thyroid Cancer. Journal of Clinical Oncology 2018; 36 :7–13. Capdevila J, et al. PD-1 Blockade in anaplastic thyroid carcinoma. Journal of Clinical Oncology 38, no. 23 (August 10, 2020) 2620–2627. Cabanillas ME, et al. Atezolizumab combinations with targeted therapy for anaplastic thyroid carcinoma (ATC). Journal of Clinical Oncology 2020;38(15). Iyer PC, et al. Salvage pembrolizumab added to kinase inhibitor therapy for the treatment of anaplastic thyroid carcinoma. J Immunother Cancer 2018;6 :68.